P170 Changes in the epidemiology of lung cancer in a hospital in London, UK between 2000 and 2012. (19th November 2012) - Ward, K; Rao, D; Birring, SS; Lal, R; Desai, S; Ahmad, S; Pomplun, S; Kelly, J; Atuchar, I; Barker, RD
Abstract : Background: Changes in the epidemiology of lung cancer could have important implications for treatment and prognosis. International studies have suggested adiminishing gap between the incidence of lung cancer in men and women and an increasing proportion of adenocarcinomas. 1 We examined our own cohort of patients from a teaching hospital in south London UK to see whether these observations could be replicated. Methods: All patients with suspected intra-thoracic malignancy were logged in a bespoke database. Relevant parameters were recorded. Data items were defined according to the specifications of the Lucada dataset. Stage was coalesced into "Early" (1–2a), "locally advanced" (3a, 3b) and advanced (4). Analysis was restricted to the major cell types squamous cell, adenocarcinoma, small cell and probable lung cancer unknown histology, first seen between January 1st 2000 and January 1st 2012. We analysed age, sex, histological cell type, stage and performance status by epoch. The results were tabulated and examined visually and using the chi-square test. Age was examined using one-way Anova. We used SPSS for MAC V19. Results: One thousand three hundred and fifty patients met the entry criteria. Variables were distributed as follows; 839 men (62%), median age 71 years (inter quartile range 61–78), squamous cell 474 (35%), adenocarcinoma 404(30%), small cell (12%), probable cancer unconfirmed histologically 307(23%). early stage 234 (17%), locally advanced 366 (27%), advanced 620 (46%), not staged 130 (10%). Performance status 0–262 (19%), 1–38829(%), 2–290 (21%), 3–213 (16%), 4–111 (8%), not staged 86 (6%). The proportion of patients with squamous cell carcinoma decreased from 47% to 24% and the proportion with adenocarcinoma increased from 21% to 45% (p<0.001). The proportion of patients with lung cancer who were women rose from 28% to 44% (p=0.02). No temporal changes were seen in the other variables. Discussion: There have been dramatic changes in the epidemiology of lung cancer in our hospital over a 12 year period. The significance of these changes for treatment and prognosis should be explored. Devesa SS, Bray F, Vizcaino AP, Parkin DM. International lung cancer trends by histologic type: Male: Female differences diminishing and adenocarcinoma rates rising. International Journal of Cancer 2005; 117(2):294–99.